Support Schemes in Renewable Energy: Commentary to Judgment of the Court (Fifth Chamber) of 13 September 2017, ENEA S.A. v. Prezes Urzędu Regulacji Energetyki - Nevin Alija (Market and Competition Law Review)
In its September 13th 2017 decision,1 the Court of Justice of the European Union (CJEU) decided on a request for a preliminary ruling by the Supreme Court of Poland (Sąd Najwyższy) in proceedings between ENEA S.A. (ENEA) and the president of the Urzędu Regulacji Energetyki (Office for the regulation of energy, URE) on the imposition by the latter of a financial penalty on ENEA for breach of its obligation to supply electricity produced by cogeneration. The judgment of the Court of Justice follows many decisions of the European Commission and judgments of the EU courts assessing the involvement of State resources in support schemes in energy, particularly with the aim of switching towards more environmentally friendly sources. This case reaffirms that support schemes may, in certain circumstances, fall outside the scope of the EU State aid rules.